The Effort Increasing Scientific Literacy of Zam Zam Muhammmadiyah Cilongok Modern Islamic Boarding School - Maauun, Haudh Al (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2023)
Purpose: Determine the participation of students and teachers at the Zam Zam Muhammadiyah Cilongok Modern Islamic Boarding School in seminar activities and scientific publications. Methodology: The qualitative methods with a literature study approach. Data sources from www.google.scholar and www.sinta.kemdikbud.ac.id published articles in 2016-2023 use the words "Pesantren Zam Zam Muhammadiyah Cilongok", while data analysis uses content analysis techniques. Results: From the 15 published articles, 1 national journal article was indexed by Google Scholar, 1 national seminar proceeding article was indexed by Google Scholar, 1 international seminar proceeding was indexed by Google Scholar and 12 reputable national journal articles were indexed by SINTA 3, 4, 5 and 6. The author's affiliation is not as a student or teacher at the Zam Zam Muhammadiyah Cilongok Modern Islamic Boarding School. Efforts are needed to increase scientific literacy at the Zam Zam Muhammadiyah Islamic boarding school by achieving scientific literacy indicators. Efforts to increase seminar activities through teacher competency, student interest, self-confidence and language mastery skills. Meanwhile, efforts to increase scientific publications include the promotion of Islamic boarding schools, recommendations for scholarships, and training in scientific publications. Implication: Better scientific literacy for students and teachers at the Zam Zam Muhammadiyah Cilongok Islamic boarding school will increase participation in seminar activities and scientific publications Applications/Originality/Value: the importance of assessing scientific literacy in modern Muhammadiyah Islamic boarding schools to increase participation in seminars and scientific publications.